Influence of Problem Based Learning Model on Student Mental Models - Batlolona, J. R.; Singerin, S.; Diantoro, M. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2020)
The purpose of this study was to determine the development of mental models (MM) of students as well as to analyze the differences in MM based on the learning model used. This research is expected to be a guide for teachers in exploring the concept of physics as a whole. The study was conducted at the high school level with a medium level school category. The research method used mixed methods embedded experimental models with surface level, matching and deep (SMD) diagnostic test instruments. The results of the study showed that there were an increase on students’ MM at each meeting in the SMD level. Other results show that there are differences in the mean scores corrected between levels of the learning model. The mean score corrected PBL mental model is significantly different from conventional. The increase in MM students with PBL was higher than the increase in MM students with conventional learning. Thus, PBL can be recommended to increase MM students' physics of high school students.